The new confessions of an economic hit man - Perkins, John 1945- (Berrett-Koehler Publishers, 2016)
"Featuring 12 explosive new chapters, this new edition of the New York Times bestseller brings the story of Economic Hit Men up-to-date and, chillingly, home to the U.S.--but it also gives us hope and the tools to fight back"--Provided by publisher
Includes bibliographical references and index. - Print version record
Keywords: Perkins, John -- 1945-; United States -- National Security Agency -- Biography; Chas. T. Main, Inc; World Bank -- Developing countries; Intelligence officers -- Biography -- United States; Economists -- Biography -- United States; Energy consultants -- Biography -- United States; Corporations, American -- Corrupt practices; Imperialism -- History -- 20th century; Imperialism -- History -- 21st century; Perkins, John; 1945-; United States; National Security Agency; World Bank; 1900-2099; Officiers de renseignements; États-Unis; Biographies; Économistes; États-Unis; Biographies; Consultants en énergie; États-Unis; Biographies; Impérialisme; Histoire; 20e siècle; Impérialisme; Histoire; 21e siècle; BIOGRAPHY & AUTOBIOGRAPHY; General; BUSINESS & ECONOMICS; Finance; Corporations, American; Corrupt practices; Economists; Energy consultants; Imperialism; Intelligence officers; Developing countries; United States; autobiographies (literary works); Autobiographies; Biographies; History